1. Usuń nawiasy i wykonaj redukcję wyrazów podobnych.

a) (2x² + 4x - 3) + (-x² - 2x + 4) =
b) (3/5m² + 2/3n² + 6) + (-1/3m² - 2/3n² - 2⅖) =
c) (0,5xy² - 1,2y² + 5) + (-0,8y² - 2,5xy² - 2⅛) =

3/5 |
2/3 |
-1/3 |-------> to ułamki
2/3 |
2⅖ |
2⅛ |

z góry dzięki :)

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T16:10:12+01:00
A) 2x²+4x-3-x²-2x+4=x²+2x+1
b)3/5m²+2/3n²+6-1/3m²-2/3n²-2²/₅=9/15m²-5/15m²+3³/₅ (+2/3n²-2/3n² wychodzi 0, więc się tego nie pisze)
c)0,5xy²-1,2y²+5-0,8y²-2,5xy²-2¹/₈=-2xy²-2y²+2⁷/₈
  • zaki
  • Początkujący
2010-03-17T16:19:32+01:00
A)=2x²+4x-3-x²-2x+4=x²+2x+1
b)=9/15m²+2/3n²+6-5/15m²-2/3n²-2²/₅=4/15m²+3³/₅
c)=0,5xy²-1,2y²+5-0,8y²-2,5xy²-2⅛=-2xy²-2y²+2⅞